2019
DOI: 10.3389/fmicb.2019.01546
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Regulation of Extracellular Superoxide Production by the Coccolithophore Emiliania huxleyi (CCMP 374)

Abstract: In marine waters, ubiquitous reactive oxygen species (ROS) drive biogeochemical cycling of metals and carbon. Marine phytoplankton produce the ROS superoxide (O 2 − ) extracellularly and can be a dominant source of O 2 − in natural aquatic systems. However, the cellular regulation, biological functioning, and broader ecological impacts of extracellular O 2 − production by marine phytoplankton remain myst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
(170 reference statements)
1
5
0
Order By: Relevance
“…These correlations implicate eukaryotic phytoplankton as important contributors to particle‐associated ROS. This is consistent with previous studies that have demonstrated that eukaryotic phytoplankton produce extracellular superoxide at the highest rates of any widespread marine microbe and are known to produce extracellular superoxide in the dark (Diaz et al, 2019; Plummer et al, 2019; Rose et al, 2008b; Sutherland et al, 2019). Interestingly, Synechococcus abundance across all stations does not correlate to superoxide production rate (Figure 5), suggesting that eukaryotic phototrophs play a much more dominant role in ROS production in this coastal setting.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These correlations implicate eukaryotic phytoplankton as important contributors to particle‐associated ROS. This is consistent with previous studies that have demonstrated that eukaryotic phytoplankton produce extracellular superoxide at the highest rates of any widespread marine microbe and are known to produce extracellular superoxide in the dark (Diaz et al, 2019; Plummer et al, 2019; Rose et al, 2008b; Sutherland et al, 2019). Interestingly, Synechococcus abundance across all stations does not correlate to superoxide production rate (Figure 5), suggesting that eukaryotic phototrophs play a much more dominant role in ROS production in this coastal setting.…”
Section: Discussionsupporting
confidence: 92%
“…Microbes produce extracellular superoxide via membrane bound and transmembrane oxidoreductase enzymes. This avenue of extracellular ROS production has been documented across the domains of Bacteria and Eukarya, including phototrophs and heterotrophs (Diaz et al, 2013Hansel et al, 2016;Plummer et al, 2019;Rose et al, 2008b;Sutherland et al, 2019). Within eukaryotic phytoplankton, the transmembrane NOX family NADPH-oxidases have been implicated in extracellular ROS production (Anderson et al, 2016;Kustka et al, 2005;Saragosti et al, 2010).…”
Section: Controls On Superoxide Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dark superoxide production rates compiled in this study, with the exception of coccolithophores, were measured from cells grown to midexponential phase under ideal growth conditions using a flow-injection chemiluminescent approach (9). The study investigating the cell-specific superoxide production rate of coccolithophores measured their production rate throughout their growth curve, which we converted to a time-weighted average using trapezoidal integration of the cell superoxide production rate as a function of time (18). Cell-normalized superoxide production rates presented in the scientific literature are either presented as net or gross superoxide production rates, the latter requiring an exogenous spike of superoxide to determine the proportion of extracellular ROS that is enzymatically degraded by the organisms.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, dark (lightindependent) particle-associated superoxide production accounts for a significant fraction of superoxide measured in natural waters within both the photic and aphotic zone (9,10). Dark, extracellular superoxide production is in fact prolific among marine heterotrophic bacteria, cyanobacteria, and eukaryotes (9,(11)(12)(13)(14)(15)(16)(17)(18). Production of extracellular superoxide proceeds via a one-electron transfer initiated by transmembrane, outer membrane-bound, or soluble extracellular enzymes thought to belong generally to NAD(P)H oxidoreductases (19), and more recently to heme peroxidases and glutathione reductases (9,20,21).…”
Section: •-mentioning
confidence: 99%